Prinsip Keadilan dalam Praktik Poligami: Analisis Hukum Islam dan Hukum Positif di Indonesia - Muhammad Rizwar Azis; M. Dwi Agam Rifa’i; Fauzan Ainur Habib; Dera Jaidda Dzahabiyyah (STIKes Ibnu Sina Ajibarang, 2026)
This study discusses the concept of polygamy from the perspectives of Islamic law and positive law in Indonesia, focusing on the principles of justice and its impact on women and families. Polygamy is one of the issues in fiqh munakahat that continues to generate debate because it is considered closely related to patriarchal culture, gender inequality, and violence against women. This study aims to analyze the legal basis of polygamy in the Qur’an, the views of scholars of tafsir and fiqh regarding polygamy, as well as the regulation of polygamy in Indonesian legislation. This study employs a library research method with a normative-sociological approach. Data sources were obtained from books of tafsir, fiqh, hadith, Islamic legal literature, and laws and regulations related to marriage in Indonesia. The findings indicate that Islam permits polygamy under very strict conditions, particularly regarding the husband’s ability to act justly both materially and emotionally. However, justice in emotional aspects and affection is considered very difficult for ordinary people to achieve, as emphasized in Qur'an Surah An-Nisa verse 129. In Indonesian positive law, the primary principle of marriage is monogamy, while polygamy is only permitted under certain circumstances with administrative requirements and court approval. This study concludes that the practice of polygamy in the modern era should be understood contextually by considering aspects of public welfare (maslahah), the protection of women’s rights, family justice, and the primary objectives of Islamic law in establishing a harmonious family characterized by sakinah, mawaddah, and rahmah.